The English - Vietnamese translation of financial and banking terminologies in the book “English for finance and banking” by associate professor Nguyễn Xuân Thơm = Cách dịch các thuật ngữ tài chính – Ngân hàng từ tiếng anh sang tiếng việt trong cuốn “Tiếng anhTài chính Ngân hàng” của PGS.TS Nguyễn Xuân Thơm - Vũ, Văn Duy (2021)
This paper investigated the English – Vietnamese translation of financial and banking terminologies provided in the book “English for Finance and Banking” written by Associate Professor Nguyễn Xuân Thơm in 1999. The study was conducted to find out the translation procedures and the most dominant one that were employed in translating financial and banking terminologies in the above-mentioned book. To achieve this aim, qualitative and quantitative methods were utilized. Through data collection and analysis, the research revealed the translation procedures and the most dominant one being applied to translate terminologies in the book. Overall, five translation procedures of calque, literal translation, equivalence, transposition and borrowing, among which calque was the most dominant, were found in the English – Vietnamese translation of terminologies in the book. However, there are still limitations that leave room for improvements in the study. Finally, some suggestions for further studies were offered.